Italian Asset Managers? Behavior: Evidence on Overconfidence, Risk Taking and Gender - Daniela Beckmann; Torben Lütje; Luca Rebeggiani (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2007)
This paper offers new insights into the Italian mutual fund industry. Surveying Italian professionals, we do not only reveal typical gender differences but also detect divergence to their German counterparts. While disclosing Italian professionals? overly positive self-assessment in general, we find evidence for male overconfidence in particular – though without being accompanied by excessive control illusion of the own information level. Asset managers? risk taking reveals further differences: Italian female professionals do not only assess themselves as more risk averse than their male colleagues, they also prefer a more passive portfolio management compared to the level they are allowed to. Moreover, in a tournament scenario near the end of the investment period female asset managers do not try to become the ultimate top performer when they have outperformed their peer group so far. However, in case of underperformance, the risk of deviating from the benchmark makes especially female professionals willing to seize a chance of catching up. Overall, compared to their German counterparts, we find Italian asset managers to be slightly more risk averse. Matching bounded former results on Italian mutual funds, we discuss interdependencies as well as impact of our findings at the individual asset managers? level on trading activity, management style and performance. – – Il presente studio si inserisce nel filone della finanza comportamentale e analizza il comportamento dei gestori italiani di fondi d?investimento. Esso si basa su una vasta inchiesta condotta nel 2004, con la quale ? stato raccolto uno dei pi? ampi campioni di questionari nel settore dei gestori professionistici. L?analisi ? focalizzata principalmente su due aspetti: le differenze di comportamento tra i due sessi e il confronto con le attitudini dei gestori di fondi in Germania, dove un?analoga inchiesta ? stata svolta nello stesso periodo. Numerosi risultati interessanti emergono: prima di tutto, una spiccata tendenza all?overconfidence, cio? all?iper-sicurezza, riscontrabile soprattutto tra i gestori maschi, mentre le donne non solo si dimostrano pi? consce dei propri limiti e meno propense al rischio, ma tendono anche ad utilizzare uno stile di trading pi? passivo. Questi risultati sono ulteriormente confermati dalle risposte date a domande mirate a creare scenari da torneo. Paragonati al comportamento dei loro colleghi tedeschi, i gestori italiani dimostrano di essere leggermente pi? avversi al rischio.
Keywords: J16; G14; G23; 330; Institutional investors; Gender; Overconfidence; Risk taking; Tournament behavior